Pełnomocnik Rządu do Spraw Pokojowego Wykorzystania Energii Jądrowej.Pozycja ustrojowa, zakres działania, kompetencje i zadania - Młynarkiewicz, Kamil (PRAWO i WIĘŹ, 2026)
The aim of this paper is an analysis of the evolution of the statutory position, competences, and organizational structure of the Government Plenipotentiary for the Peaceful Use of Nuclear Energy in the years 1956–1973. Based on an analysis of archival legal acts – resolutions of the Council of Ministers, statutes, and internal organizational regulations – the genesis of the office is traced, which was established by Resolution No. 444/56 to solve the problem of coordinating activities undertaken by the Polish Academy of Sciences and the economic ministries. The paper demonstrates two fundamental phases of the office’s transformation.